Pengaruh Fear of Missing Out (FoMO) terhadap Perilaku Konsumtif pada Mahasiswi Pembeli Barang Diskon Aplikasi Shopee - Safitri, Adinda Fobi; Rinaldi, Rinaldi (AHKAM, 2023)
People spend a significant amount of their time constantly checking their social media and online market accounts. Individuals who always feel afraid of missing out demonstrate a tendency toward FoMO. However, the desire to belong to a group or purchase a product leads individuals to act consumeristically. This study aims to investigate the impact of Fear of Missing Out on compulsive buying behavior among female university students who purchase discounted items using the Shopee application. The population consists of female students at the State University of Padang. Purposive sampling was used to select a sample of 165 individuals. The study utilized the Fear of Missing Out scale (ONFoMO), which was modified from Kurniawan and Utami's work (2022), alongside the Consumptive Behavior scale based on Sumartono's indicators (2002). The simple linear regression analysis revealed a correlation coefficient (R) of 0.779 with a significant value of .000 (p<0.05) and an influence of 60.7%. Thus, a significant positive influence of Fear of Missing Out (FoMO) on consumer behavior among female college students buying discounted products was observed. In conclusion, it can be inferred that the higher the level of Fear of Missing Out (FoMO), the higher the likelihood of consumer behavior among female college students buying discounted products, and vice versa.